ANALISIS PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA GURU PADA SEKOLAH GLOBAL MANDIRI - Herni Pujiati (JABE (Journal of Applied Business and Economic), 2015)
This study entitled "Analysis of Effect on Performance Leadership and Compensation teacher at the School of Global Mandiri" The aim of this study was to determine and prove how much influence between leadership and compensation to the performance of teachers At Sekolah Global Mandiri. In this study uses survey research methods with the correlational approach, predictive and explanatory. By taking a sample of 81 people were identified as teacher. To solve problems by analyzing and testing the relationship and influence between the independent variables on the dependent variable used models kausalistik through regression analysis with SPSS 14.0